Risk factors for human papillomavirus‐positive nonoropharyngeal squamous cell carcinoma. Issue 8 (26th February 2020) - Windon, Melina J.; D'Souza, Gypsyamber; Waterboer, Tim; Rooper, Lisa; Westra, William H.; Troy, Tanya; Pardoll, Drew; Tan, Marietta; Yavvari, Siddhartha; Kiess, Ana P.; Miles, Brett; Mydlarz, Wojciech K.; et al.
Abstract: Background: Human papillomavirus (HPV)‐positive oropharyngeal cancer (HPV‐OPC) is distinct from HPV‐unassociated head and neck cancer. However, whether risk factors for HPV‐positive oropharyngeal and nonoropharyngeal squamous cell cancer are the same is unclear. Methods: Incident cases of HPV‐positive head and neck cell cancer and matched non‐cancer controls were enrolled in a multi‐institutional, prospective study examining risk factors, biomarkers, and survival. Results: HPV‐nonOPC (n = 20) were more likely to be ever smokers than controls (n = 80, OR 3.49, 95%CI 1.11‐10.9) and HPV‐OPC (n = 185, OR 3.28, 95%CI 1.10‐10.2). Compared with HPV‐OPC, HPV‐nonOPC were less likely to have had over 3 oral sexual partners (OR 0.29, 95%CI 0.06‐0.9), more likely to have multimorbidity (OR 3.30, 95%CI 1.04‐10.5), and less likely to have antibodies to HPV16 E6 (90% vs 28%, OR 0.05, 95%CI 0.02‐0.2). HPV‐nonOPC had worse 4‐year OS (77% vs 96%, P = .001) and RFS (69% vs 94%, P < .001) than HPV‐OPC. Conclusions: HPV‐positive nonoropharyngeal are distinct from HPV‐positive oropharyngeal cancers.